The effect of magnetic field on the impurity binding energy of shallow donor impurities in a Ga1−xInxNyAs1−y/GaAs quantum well (2012)
ABSTRACT: Using a variational approach, we have investigated the effects of the magnetic field, the impurity position, and the nitrogen and indium concentrations on impurity binding energy in a Ga1−xInxNyAs1−y/GaAs quantum well. Our calculations have revealed the dependence of impurity binding on the applied magnetic field, the impurity position, and the nitrogen and indium concentrations.